VIRTUAL PANORAMA LANDING DAN TAKE OFF BANDARA ADI SUMARMO SOLO - Nurcahyani Dewi Retnowati; Muhammad Zainal Muttaqim (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
The development of information technology and lead to intense competition in all areas, many parties began implementing a strategy to improve services. Information obtained from various sources such as the Internet can make it easier to determine the state o f a place or vehicle that will be addressed, but a lot of information from various sources, it only displays a static image that is not enough to describe the situation as a whole as well as the environment, it is necessary for the proper media fo r representing the information. One type of appropriate multimedia effective dam to provide information or a description of the location of these is to use virtual panoramic view. Not like a video that is merely one direction (forward grooved) virtual panoramic view is designed to allow the user to interact directly with the environment to crawl closer and more interactive. Final results from this aplication is a multimedia display that can be applied in any kind o f media because using ActionScript for basic program so that it can be applied via online websites or interactive CDs or display advertising.